A Perspective on Hypericum perforatum Genetic Transformation - Hou, Weina; Shakya, Preeti; Franklin, Gregory (Frontiers in Plant Science, 2016)
Hypericum perforatum (St John’s wort) is a reservoir of diverse classes of biologically active and high value secondary metabolites, which captured the interest of both researchers and the pharmaceutical industry alike. Several studies and clinical trials have shown that H. perforatum extracts possess an astounding array of pharmacological properties. These properties include antidepressant, anti-inflammatory, antiviral, anti-cancer and antibacterial activities; and are largely attributed to the naphtodianthrones and xanthones found in the genus. Hence, improving their production via genetic manipulation is an important strategy. In spite of the presence of contemporary genome editing tools, genetic improvement of this genus remains challenging without robust transformation methods in place. In the recent past, we found that H. perforatum remains recalcitrant to Agrobacterium tumefaciens mediated transformation partly due to the induction of plant defense responses coming into play. However, H. perforatum transformation is possible via a non-biological method, biolistic bombardment. Some research groups have observed the induction of hairy roots in H. perforatum after Agrobacterium rhizogenes co-cultivation. In this review, we aim at updating the available methods for regeneration and transformation of H. perforatum. In addition, we also propose a brief perspective on certain novel strategies to improve transformation efficiency in order to meet the demands of the pharmaceutical industry via metabolic engineering.